Pedicle screw pull-out strength between the Jamshidi needle and pedicle probe techniques in an osteoporotic cancellous bone model: a biomechanical study - Tharmaseelan, Shival; Harun, Mohd Hezery; Mohamed Ramlee, Fadzrul Abbas; Abdullah, Mohd Na'im (Springer, 2024)
Introduction: Spinal fusion surgery with pedicle screws is commonly performed to stabilize the spine of osteoporotic patients. However, securing a strong screw fixation in osteoporotic bone presents significant challenges due to the reduced bone density. This study aimed to compare the biomechanical performance in an osteoporotic bone model of pedicle screws inserted using two different techniques, the Jamshidi needle technique and the pedicle probe technique, as well as the influence of tapping on both these techniques. The research sought to determine if the surgical device used in aiding pedicle screw placement, pedicle probe (open technique) and Jamshidi needle (minimally invasive surgical (MIS) technique), affects the eventual stability of the screw in osteoporotic conditions. The findings of this study could enlighten surgical practices, potentially leading to improved clinical outcomes for patients suffering from osteoporosis-related spinal instability. Materials and methods: An in vitro biomechanical comparative study was performed whereby pedicle screws were inserted into a standardized polyurethane foam model of grade 10, mimicking osteoporotic bone. Cylindrical poly-axial pedicle screws of 6.5 mm diameter and 45 mm length made out of medical-grade titanium alloy, Ti-6Al-4V, were inserted using four different techniques: Jamshidi needle, Jamshidi needle with tapping, pedicle probe, and pedicle probe with tapping. The screws were inserted in a standardized manner across all groups; the constructs were subsequently attached to the Material Testing System (MTS) 810 machine (MTS Systems Corporation, Eden Prairie, Minnesota, United States) using a customized jig. A direct-load-to-fail test was performed, where data was collected and tabulated into a force-displacement graph. The axial pull-out strength, axial stiffness, and displacement to failure of each construct were then extracted from the graph. Independent samples t-test was then used to compare and study the association between the groups. Results: The pedicle probe technique demonstrated superior pull-out strength (698.36±16.34 N) compared to the Jamshidi needle technique (557.15±4.52N) (p<0.05). A greater displacement to failure was also seen in the pedicle probe group (2.26±0.04 mm) versus the Jamshidi needle group (1.18±0.06 mm) (p<0.05). However, the Jamshidi needle technique exhibited higher axial stiffness (336.88±23.24 N/mm) compared to the pedicle probe technique (208.82±7.82 N/mm) (p<0.05). In examining the influence of tapping on both techniques, results show significantly reduced pull-out strength and displacement to failure in the pedicle probe group. Conclusions: The pedicle probe technique offers enhanced initial stability in the osteoporotic bone as evidenced by the superior pull-out strength and displacement to failure. On the other hand, the Jamshidi needle technique provides greater resistance to deformation, demonstrated by higher axial stiffness. Tapping should be carefully considered, especially while using the pedicle probe technique, as demonstrated by significantly reduced pull-out strength and displacement to failure. The choice of technique should be informed by specific clinical context balancing the need for initial stability, resistance to deformation, and risk of screw failure.